Democrats, authoritarians and the Bologna process : universities in Germany, Russia, England and Wales - Marquand, Judith (Emerald Publishing, 2018)
This book sets the extraordinary phenomenon of The Bologna Process in its historical and political context. Four contrasting country case studies - Germany, Russia, England, Wales - illustrate some of the varying responses adopted when faced with a similar framework.